2006
DOI: 10.5993/ajhb.30.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Ways to Say No: Refusal Skill Strategies Among Urban Adolescents

Abstract: Objectives: To examine associations among adolescents' generated verbal strategies (ie, Simple No, Declarative Statements, Excuse, Alternatives) and underlying nonverbal assertiveness in 2 refusal situations: smoking and shoplifting. Methods: Sixth-grade urban minority students (N = 454) participated in videotaped role-play assessments of peer refusal skills. Results: Differences were found by situation with students demonstrating greater use of Simple No in the smoking refusal and Alternatives in the shoplift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
1
16
0
9
Order By: Relevance
“…Prevention programs that expand to include skill-building about healthy sexual communication and boundaries show promise in preventing the full continuum of sexual aggression (Carmody, 2005;Heppner, Humphrey, Hillenbrand-Gunn, & DeBord, 1995;Nichols, Graber, Brooks-Gunn, & Botvin, 2006). For example, Muehlenhard, Andrews, and Beal (1996) identified that females who communicated early in the interaction about sexual boundaries were more likely to be believed.…”
Section: Implications For Preventionmentioning
confidence: 99%
“…Prevention programs that expand to include skill-building about healthy sexual communication and boundaries show promise in preventing the full continuum of sexual aggression (Carmody, 2005;Heppner, Humphrey, Hillenbrand-Gunn, & DeBord, 1995;Nichols, Graber, Brooks-Gunn, & Botvin, 2006). For example, Muehlenhard, Andrews, and Beal (1996) identified that females who communicated early in the interaction about sexual boundaries were more likely to be believed.…”
Section: Implications For Preventionmentioning
confidence: 99%
“…However, there are national surveys that show an association between better performance in SSI factor F1 and involvement with certain substances, such as crack (SCHNEIDER; ANDRETTA, 2017b; SÁ; DEL PRETTE, 2014) and tobacco (RONDINA et al, 2013(RONDINA et al, , 2015. There are also other studies that have shown an inverse association between smoking and assertiveness (NICHOLS et al, 2006;EPSTEIN et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…O conjunto dos resultados denota controvérsia, no tocante à associação entre tabagismo e o comportamento assertivo em geral. Em alguns trabalhos, adolescentes com baixa assertividade apresentaram mais probabilidade de serem tabagistas (Epstein, et al 2000;Nichols, et al 2006). No trabalho de Suelves e Sanches-Turet, (2001) não foi encontrada associação entre tabagismo e essa habilidade.…”
Section: Discussionunclassified
“…É crescente o número de estudos enfocando (entre outros aspectos) a relação entre repertório de habilidades sociais e o aparecimento e/ou progressão de transtornos relacionados ao abuso de drogas lícitas e ilícitas (Epstein, Griffin, & Botvin, 2000;Nichols, Graber, Brooks-Gunn, & Botvin, 2006;Palos, Barrera, Martinez, Oviedo, & Oca, 2009;Wagner & Oliveira, 2009). Supõe-se ainda, que déficits em habilidades sociais possam tornar o indivíduo predisposto ou vulnerável à dependência de substâncias psicoativas em geral, pois, como Pinho e Oliva (2007) afirmam: muitos dependentes percebem a si mesmos como incapazes de lidar com situações sociais de conflito.…”
unclassified